MT2A promotes angiogenesis in chronically ischemic brains through a copper–mitochondria regulatory mechanism - Ni Mo; Chuyang Tai; Yang Yang; Cong Ling; Baoyu Zhang; Lei Wei; Cian Yao; Hui Wang; Chuan Chen (Journal of Translational Medicine)
Abstract Background Approximately half of patients with chronic ischemic cerebrovascular disease (CICD) exhibit poor revascularization. Metallothionein 2 A (MT2A) has a high affinity for metal ions and is potentially capable of chelating toxic copper ions to alleviate the impairment of angiogenesis. Therefore, we hypothesized that MT2A could promote angiogenesis in chronically ischemic brains by neutralizing excessive copper ions during copper overload (CPO). Methods We first collected dura matter (DM) samples from CICD patients and examined the expression of cuproptosis-related genes (DLAT, FDX1, and SDHB) to confirm the inhibitory effect of CPO on angiogenesis. Then, we treated human umbilical vein endothelial cells (HUVECs) with different concentrations of elesclomol and CuCl2 to determine the optimal concentration for inducing CPO. HUVEC activity and mitochondrial structure and function were detected to explore the ability of MT2A to alleviate CPO-induced damage. Finally, a rat model of 2-vessel occlusion plus encephalo-myo-synangiosis (2VO + EMS) with CPO was established to test the proangiogenic effect of MT2A through the copper–mitochondria regulatory mechanism in chronically ischemic brains. Results Compared with those from Matsushima grade A patients, DM samples from Matsushima grade C patients presented significantly greater DLAT and FDX1 expression and significantly lower SDHB expression. The optimal drug concentration for inducing CPO was subsequently determined, and in vitro experiments revealed that HUVEC activity was significantly decreased in the CPO group under hypoxic culture, accompanied by increased DLAT oligomerization, decreased SDHB expression, increased HSP70 expression. Moreover, significantly more common mitochondrial aberrations and significantly lower mitochondrial activity were detected in the CPO group compare with the control group. Additionally, MT2A overexpression alleviated CPO-induced mitochondrial dysfunction and cytotoxicity, improving HUVEC viability. In vivo, a CPO rat model was established, and CPO inhibited cerebral angiogenesis in 2VO + EMS model rats. Moreover, significantly greater CD31 expression, less DLAT accumulation, more mitochondria, and fewer mitochondrial abnormalities were observed in the CPOMT2A+ group than in the CPO group, accompanied by significantly improved cerebral blood perfusion and cognitive function. Conclusion MT2A can promote angiogenesis in chronically ischemic brains by neutralizing excessive copper ions and rescuing CPO-induced mitochondrial dysfunction.